Follow-Up of Cardiopulmonary Responses Using Submaximal Exercise Test in Older Adults with Post-COVID-19 - Patchareeya Amput; Sirima Wongphon (Annals of Geriatric Medicine and Research)
Background Data on cardiopulmonary fitness in older adults in the longer term after coronavirus disease 2019 (COVID-19) are of interest as the time required for the full recovery of physical fitness after COVID-19 remains unclear. Some studies have reported that patients do not recover physical fitness for up to 6 or 12 months after COVID-19, whereas other studies have observed full recovery after 12-months. Therefore, this study evaluated and compared the cardiopulmonary responses induced by the 6-minute walk test (6MWT) and 1-minute sit-to-stand-test (1-min-STST) results at 3, 6, and 12 months in older adults with and without COVID-19. Methods This study included 59 older adults aged ≥60 with and without a history of COVID-19. The cardiopulmonary response parameters including heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse oxygen saturation (O2 sat), rate of perceived exertion (RPE), and leg fatigue were evaluated in the participants after 6MWT and 1-min-STST assessments. Results Post-COVID-19, older adults showed statistically significant differences in HR, SBP, DBP, O2 sat, RPE, leg fatigue, 6MWT time, and 1-min-STST step numbers at 3, 6, and 12 months (p<0.001). Moreover, older adults showed statistically significant differences in HR, SBP, DBP, RPE, leg fatigue, O2 sat, and 6MWT distance at 3 months post-COVID-19 compared with those in older adults without COVID-19 (p<0.001). Conclusion While older adults showed recovery of cardiopulmonary response parameters according to 6MWT and 1-min-STST findings at the 12-month follow-up post-COVID-19, these results of these measurements did not return to the values observed in older adults without COVID-19.